2005
DOI: 10.1081/cbi-200041046
|View full text |Cite
|
Sign up to set email alerts
|

Increased Occurrence of Out‐of‐Hospital Cardiac Arrest on Mondays in a Community‐Based Study

Abstract: Acute myocardial infarction and sudden cardiac death are more common on Mondays than other days of the week. The stress of returning to work at the beginning of the week has been postulated as a possible trigger factor. This project examined the weekly variation of out-of-hospital cardiac arrests of nontraumatic origin for the entire case series as well as for selected subgroups. A retrospective analysis of 1,498 incidences between January 1, 1995 and December 31, 1996 revealed a distinct Monday peak in occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 29 publications
1
16
4
Order By: Relevance
“…It has also been found that if the first day of the week (Monday) is a holiday, for example Easter or White Monday, the incidence of events is significantly lower. Some researchers found that the Monday peak is most pronounced in the working population [9,21]. Differentiation between actively working or inactive patients could not be made in our present database.…”
Section: Discussioncontrasting
confidence: 65%
“…It has also been found that if the first day of the week (Monday) is a holiday, for example Easter or White Monday, the incidence of events is significantly lower. Some researchers found that the Monday peak is most pronounced in the working population [9,21]. Differentiation between actively working or inactive patients could not be made in our present database.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, the results do not reflect accumulating work stress and workload during the work period. The slight but significant increase in relaxation percentage from Day 1 to Day 2 might rather relate to the increased stress of returning to work in the beginning of the week (Gruska et al, 2005). In contrast to that, the activity score from wrist movement for Day 2 was even slightly higher than for Day 1 meaning that differences in physical activity cannot explain this finding.…”
Section: Relaxation Measurescontrasting
confidence: 63%
“…9,10,25,26 Although the reasons remain speculative, changes in behavior around weekends, including alcohol intake, sleep/wake cycle, and physical activity may partly explain this observation. 27 In contrast to previous studies, 8 we did not observe significant variability in survival after OHCA by day of week.…”
Section: Circaseptan Variability In Incidence and Outcomesmentioning
confidence: 99%